A versatile method for preparing well-defined polymers with aggregation-induced emission property. (5th December 2018) - Wu, Ying; Qu, Lin; Li, Jun; Huang, Liyan; Liu, Zhengping
Abstract: The living ring-opening metathesis polymerization (ROMP) was demonstrated as a versatile method for preparing the well-defined polymers with aggregation-induced emission (AIE) property. In this approach, the norbornene-based monomers were prepared containing side groups of varied typical AIE fluorogens such as distyrenneanthracene (M1 ), 1, 2, 3, 4, 5-pentaphenylsiole (M2 ), and tetraphenylethene derivative (M3 ). Initiating by the Grubbs third generation catalyst (G3 ), ROMP could consume all of the exemplified monomers in less than 30 min and produce the corresponding well-defined AIE polymers of poly(M1 ), poly(M2 ), and poly(M3 ) with controlled molecular weight and narrow polydispersity. By copolymerizing with the norbornene-based monomer (M4 ) having poly(ethylene glycol) (PEG) side chain, ROMP could also produce the well-defined amphiphilic AIE block copolymers such as poly(M1 )- b -poly(M4 ) and poly(M2 )- b -poly(M4 ). Compared to norbornene-based AIE monomers, the resultant polymers showed enhanced AIE property, in which the same fluorescence intensity was obtained from the lower molar concentration of AIE fluorogen inside polymers than that inside monomers. In addition, the self-assembly of amphiphilic AIE block copolymers in selective solvents produced the fluorescent nanoparticles with varied morphologies and structures including spherical micelles, cylindrical micelles, and vesicles. Graphical abstract: Highlights: ROMP was explored to prepare varied well-defined AIE polymers. Fluorescence wavelength of AIE polymers could be manipulated by varying the AIE fluorogens. Self-assembly of amphiphilic AIE block copolymers produced fluorescent nanoparticles with varied structures.